2012
DOI: 10.1159/000341495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a ‘School-Based’ Nutrition Intervention on Anthropometric Parameters and the Metabolic Syndrome in Spanish Adolescents

Abstract: Background/Aims: In adolescents, overweight and obesity are associated with an increased cardiovascular risk. The aim of this study was to determine the impact of a school-based nutritional education program (NEP) on lifestyle changes in Spanish adolescents. Methods: We selected 263 secondary school students (127 males) aged 12–16 years from Granada (Spain), who were followed up throughout 1 school year (2009–2010). At the beginning and end of the school year, data were gathered on the food consumption frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 69 publications
(39 reference statements)
0
25
0
3
Order By: Relevance
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…Table presents the intensity evaluation of studies aiming to modify behavior across different nutrition categories. Interventions in each category were highly effective: fruit and vegetable (N = 33; effective N = 27, ineffective N = 4, unknown effectiveness N = 2), general healthy eating (N = 53; effective N = 41, ineffective N = 10, unknown effectiveness N = 2), single food or food group (N = 12; effective N = 8, ineffective N = 3, unknown effectiveness N = 1), and single nutrient (N = 7; effective N = 5, ineffective N = 1, unknown effectiveness N = 1). Comparing the frequency of effective studies in different categories showed that the mean frequency of interventions in the single food or food group category was significantly higher than for the general healthy eating category (ANOVA p = .04, Tukey's post hoc test p = .03).…”
Section: Resultsmentioning
confidence: 99%
“…School is an excellent arena for health promotion and nutrition education because it reaches practically all children and adolescents. Several school‐based health promotion interventions have been conducted with varying results . Many earlier interventions relied on providing information (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier interventions relied on providing information (i.e. lectures) to increase knowledge of health‐promoting eating patterns . In addition, functional curricula, book‐ or web‐based practices, farm visits, cooking, taste lessons and sensory education have been used .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations